Long‐term survival among 5‐year survivors of adolescent and young adult cancer. Issue 16 (2nd June 2020) - Berkman, Amy M.; Livingston, J. A.; Merriman, Kelly; Hildebrandt, Michelle; Wang, Jian; Dibaj, Seyedeh; McQuade, Jennifer; You, Nancy; Ying, Anita; Barcenas, Carlos; Bodurka, Diane; DePombo, April; et al.
Abstract : Background: Although there are a growing number of survivors of adolescent and young adult (AYA) cancer, to the authors' knowledge the long‐term overall survival (OS) patterns for AYA cancer survivors are underreported. The objective of the current study was to assess the long‐term survival of AYA cancer survivors and identify factors associated with diminished long‐term survival. Methods: The authors used The University of Texas MD Anderson Cancer Center's tumor registry to identify 5‐year survivors of cancer diagnosed as AYAs (ages 15‐39 years) between the years 1970 and 2005, and who were alive 5 years after diagnosis. Kaplan‐Meier curves were used to estimate OS rates over time, and Cox proportional hazards models were fitted to evaluate the association of covariates with OS. Results: The authors identified 16, 728 individuals who were 5‐year survivors of cancer and were diagnosed as AYAs with a median follow‐up of 20.0 years. The 10‐year, 20‐year, and 25‐year OS rates were 86% (95% confidence interval [95% CI], 85%‐86%), 74% (95% CI, 73%‐75%), and 68% (95% CI, 67%‐68%), respectively, all of which were lower than the age‐adjusted estimated survival rates of the general population. Long‐term OS improved for AYAs diagnosed between 2000 and 2005 compared with those diagnosed in the prior decades ( P  < .001). Older age at the time of diagnosis, receipt of radiation, and diagnoses including central nervous system tumors and breast cancer each were associated with diminished long‐term survival. Conclusions: AYA cancer survivors have inferior long‐term survival compared with the general population. Studies investigating the prevalence and types of late treatment effects and causes of death among AYA survivors are needed to more accurately identify AYAs who are at highest risk of early or late mortality. Abstract : Although the long‐term survival of adolescent and young adult (AYA) cancer survivors diagnosed in recent decades has improved, it remains inferior to that of the general population. AYA cancer survivors require long‐term follow‐up to diagnose and treat the late side effects of cancer treatment that may be contributing to their decreased survival.